2016
DOI: 10.5604/1232406x.1225635
|View full text |Cite
|
Sign up to set email alerts
|

Individual Metabolic Differences During Dynamic Suryanamaskar

Abstract: Wstęp. Dynamiczne Surjanamaskar (DSN) jest intensywną formą praktyki jogicznej wydatkującą wielkie ilości energii. Zawiera ona w sobie znaczące profilaktycznie i terapeutycznie zdrowotne właściwości w kierunku zwalczania otyłości i usprawniania układu sercowo-naczyniowego. Celem prezentowanych badań było określenie metabolicznych uwarunkowań podczas wykonywania 60-minutowej praktyki DSN u trzech badanych. W tym celu śledzono zmiany współczynnika wymiany gazowej RER. Materiał i metody. Przedmiotem badań było tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…The intensive yoga exercise routine called Suryanamaskar (SN) has become very popular amongst yoga practitioners of the modern era. Its unique combination of asanas (postures), pranayama (yogic breathing), and dharana (fixing the mind) helps to achieve concentration [3,[13][14][15]. The dynamic version of it (DSN) focuses on the intensity with which each round is practiced.…”
Section: Dynamic Suryanamaskarmentioning
confidence: 99%
See 3 more Smart Citations
“…The intensive yoga exercise routine called Suryanamaskar (SN) has become very popular amongst yoga practitioners of the modern era. Its unique combination of asanas (postures), pranayama (yogic breathing), and dharana (fixing the mind) helps to achieve concentration [3,[13][14][15]. The dynamic version of it (DSN) focuses on the intensity with which each round is practiced.…”
Section: Dynamic Suryanamaskarmentioning
confidence: 99%
“…The dynamic version of it (DSN) focuses on the intensity with which each round is practiced. Some studies have shown that the maximum pace of DSN performance may impose a physiological burden on the body close to the maximum limit, and that energy expenditure on such occasions may exceed 14.5 MET (VO 2max = 90.36%) and may even be up to 16 MET (VO 2max = 99.22%) [16].…”
Section: Dynamic Suryanamaskarmentioning
confidence: 99%
See 2 more Smart Citations
“…Yoga addresses these aspects at the musculoskeletal, cardiovascular, psychosocial, cognitive and spiritual levels. Stec et al [57] and Stec et al [53] found that active people regularly engaging in that particular form of the fundamental yogic practices called Suryanamaskar, which combines asanas, pranayamas and a focused mind, experienced a very favorable impact on their cardiovascular function, in that they had a lowered maximal heart rate and a significantly increased stroke volume when compared to a sedentary person. Furthermore, physical activity increases the mineral density of bones; this positive association was found by Phoosuwan et al [44].…”
Section: Yoga For Geriatricsmentioning
confidence: 99%